Risk assessment of radon in drinking water in Khetri Copper Belt of Rajasthan, India. (January 2020) - Duggal, Vikas; Sharma, Samriti; Mehra, Rohit
Abstract: Exceptionally high concentrations of radon have been found in drinking water originating from hand pumps in Khetri Copper Belt of Rajasthan. Radon concentration was determined using Durridge RAD7 professional electronic radon detector. The measured radon concentration ranged from 12.5 ± 1.5 to 862 ± 38 Bq l −1 . About 35% of the drinking water samples showed radon concentrations above the European Union's parametric value of 100 Bq l −1 . The high radon concentration obtained in groundwater is due to local natural geology. The total annual effective doses due to ingestion and inhalation of radon in drinking water varied from 0.10 to 6.7 mSv y −1 for infants, 0.06–3.8 mSv y −1 for children and 0.06–4.4 mSv y −1 for adults. Highlights: We report 222 Rn conc. in 60 groundwater samples from Khetri copper belt, Rajasthan. The samples were analyzed by Durridge RAD7 professional electronic radon detector. A 35% of the groundwater samples were above the European Union's parametric value. Recorded values are quite high due to associated uranium mineralization in area.